NEUTRALITY OF ASN IN THE ELECTION OF LEGISLATIVE MEMBERS MINAHASA REGENCY DPRD IN 2024 - Bura, Arnold; Mantiri, Jeane; Polii , Polii (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This research uses descriptive qualitative methods. This research aims to describe, analyze and interpret the duties of the State Civil Apparatus (ASN) in carrying out government policies in accordance with Law number 5 of 2014 concerning ASN, and to describe, analyze and interpret the form of ASN neutrality in general elections. Data analysis was carried out through observation, interviews and documentation techniques. The results of this research show that there are still ASNs in Minahasa Regency who are involved in campaign activities and provide support to one of the legislative member candidates for the Minahasa Regency DPRD, then participate or contribute in distributing money to the community in the form of bribes to elect that candidate. So whoever receives the money must support and vote for the legislative candidate pair. However, apart from that, it turns out that ASN do not yet know, understand and understand what their duties are and the basis for the rules used regarding their duties. Due to ignorance of their duties and applicable regulations, most ASNs are directly involved in election activities and show partiality in politics, without realizing that this has violated the principle of neutrality as State Civil Apparatus.